Pengaruh Gaya Kepemimpinan dan Motivasi Kerja terhadap Kinerja Karyawan pada Bank BTN Kantor Cabang Syariah Bekasi - Mike Della Ayu Rahmawati; Zahra Zahra; Athiy Dina Rosihana (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Bank BTN Syariah Bekasi Branch is one of the Islamic banking institutions operating in Indonesia and plays an important role in providing sharia-based financial services. In running its business, this bank faces various challenges, one of which is the achievement of work targets by employees who are not optimal. The results of the performance assessment show that employee performance is still relatively low. This condition is allegedly influenced by low work motivation and leadership style that has not been able to drive maximum productivity, thus impacting operational effectiveness and achieving overall company goals. The purpose of this study is to determine the influence of leadership style and work motivation on the performance of employees of Bank BTN Syariah Bekasi Branch, the research data sources used include primary data and secondary data, the type of research data is quantitative, the number of respondents in the study is 56 respondents, the data processing method used, descriptive analysis, multiple regression analysis, determination coefficients and hypothesis tests. Based on the results of the study, it shows that the leadership style variable has a positive influence on employee performance. Meanwhile, work motivation has no effect on employee performance. Simultaneously, there is an influence of leadership style and work motivation on employee performance. This can be proven based on the recorded F value of 43,883. which means it is greater than the F value of the table of 3.175. (43,883 > 3,175). In addition, the resulting significance value is 0.000, which is smaller than the significance level of 0.05 (0.000 < 0.05).